STRATEGIC MANAGEMENT AND ORGANIZATIONAL MANAGEMENT IN AGRICULTURAL EDUCATION INSTITUTIONS - Shumilova, Iryna (Public Management and Policy, 2025)
The article explores current issues of social policy within the public administration system of Ukraine in the context of decentralization, focusing on ensuring equal access to social services for all population groups. The relevance of the research is driven by the need to adapt social policy to new challenges. Key problems identified include socio-economic instability and the consequences of the war. The objective is to identify the main problems and factors affecting the effectiveness of social service delivery. The research aims to find ways to improve social policy at the regional level. The study employs methods such as comparative analysis, statistical review, index-based approach, and social service efficiency evaluation methodology. A comparative analysis of countries like Sweden, Germany, France, and Estonia revealed effective approaches to organizing social policy, with their practices partially applicable in today’s Ukraine. The research results indicate that decentralization has expanded the financial and organizational autonomy of local communities. The war’s impact has been significant, leading to reduced institutional capacity of authorities, the destruction of social infrastructure, and workforce shortages. The article proposes a conceptual model for assessing equal access to social services, which includes five key components: social capital, economic potential, infrastructure, governance level, and digital capabilities. This model enables the evaluation of access to social services based on objective indicators while accounting for regional specificities. The practical application of this model will help identify strengths and weaknesses in social policy at the local level and determine priority areas for future development. The conclusions emphasize that improving the mechanisms of financing, organizing, and monitoring social service delivery is a crucial task today. A key consideration is the specific characteristics of regions and contemporary challenges. Future research prospects include developing new approaches to evaluating the effectiveness of social services. Additionally, future studies should focus on examining the impact of digitalization on access to social services and integrating international experience to enhance the resilience of Ukraine’s social system. It is found that the business model of an educational institution determines the degree of efficiency of its strategic management and organizational management. A model is an abstract reflection of reality that defines a set of entities and their relationships. A business model most often describes the relationship between the resources and functions of a firm and its environment. It is a contingency model that finds the optimal mode of operation for a particular market situation. An activity-based view of the business model of an educational institution allows us to link the business model to the vectors of strategic management and its participants.